Tricarbocyclic core formation of tyrosine-decahydrofluorenes implies a three-enzyme cascade with XenF-mediated sigmatropic rearrangement as a prerequisite - Zhiguo Liu; Wei Li; Peng Zhang; Jie Fan; Fangbo Zhang; Caixia Wang; Shuming Li; Yi Sun; Shilin Chen; Wenbing Yin (Elsevier, 2021)
Tyrosine-decahydrofluorene derivatives feature a fused [6.5.6] tricarbocyclic core and a 13-membered para-cyclophane ether. Herein, we identified new xenoacremones A, B, and C (1−3) from the fungal strain Xenoacremonium sinensis ML-31 and elucidated their biosynthetic pathway using gene deletion in the native strain and heterologous expression in Aspergillus nidulans. The hybrid polyketide synthase-nonribosomal peptide synthetase (PKS−NRPS) XenE together with enoyl reductase XenG were confirmed to be responsible for the formation of the tyrosine-nonaketide skeleton. This skeleton was subsequently dehydrated by XenA to afford a pyrrolidinone moiety. XenF catalyzed a novel sigmatropic rearrangement to yield a key cyclohexane intermediate as a prerequisite for the formation of the multi-ring system. Subsequent oxidation catalyzed by XenD supplied the substrate for XenC to link the para-cyclophane ether, which underwent subsequent spontaneous Diels−Alder reaction to give the end products. Thus, the results indicated that three novel enzymes XenF, XenD, and XenC coordinate to assemble the [6.5.6] tricarbocyclic ring and para-cyclophane ether during biosynthesis of complex tyrosine-decahydrofluorene derivatives.